2005
DOI: 10.1111/j.1365-2826.2005.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanotrope Cells of Xenopus laevis Express Multiple Types of High‐Voltage‐Activated Ca2+ Channels

Abstract: Pituitary melanotrope cells are neuroendocrine signal transducing cells that translate physiological stimuli into adaptive hormonal responses. In this translation process, Ca2+ channels play essential roles. We have characterised which types of Ca2+ current are present in melanotropes of the amphibian Xenopus laevis, using whole-cell, voltage-clamp, patch-clamp experiments and specific blockers of the various current types. Running an activation current-voltage relationship protocol from a holding potential (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Since we have previously shown [10]that the ω-conotoxin inhibition of the total current depends on the state of channel inactivation, we also tested the apomorphin-induced inhibition under ω-conotoxin at an HP of –30 mV, i.e., when part of the current is inhibited [10]. Compared to an HP of –80 mV, at –30 mV ω-conotoxin inhibited a larger part of the total I Ca , namely 33.7 ± 3.0% (p < 0.05), whereas for the peak and sustained currents the inhibitions were 31.7 ± 3.0 and 35.9 ± 3.4%, respectively (fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since we have previously shown [10]that the ω-conotoxin inhibition of the total current depends on the state of channel inactivation, we also tested the apomorphin-induced inhibition under ω-conotoxin at an HP of –30 mV, i.e., when part of the current is inhibited [10]. Compared to an HP of –80 mV, at –30 mV ω-conotoxin inhibited a larger part of the total I Ca , namely 33.7 ± 3.0% (p < 0.05), whereas for the peak and sustained currents the inhibitions were 31.7 ± 3.0 and 35.9 ± 3.4%, respectively (fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study we showed that Xenopus melanotropes possess all classes of HVA Ca 2+ currents. Of those only the R-type current has fast activation and inactivation kinetics [10]. Therefore, we hypothesize that at least R-type Ca 2+ currents are inhibited by D 2 -receptor activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium channels play a crucial role in determining the secretory activity of Xenopus melanotropes (Zhang et al, 2005). Melanotropes from black background-adapted toads have a 2 times larger diameter, a 2.5-fold larger membrane capacitance, a 2-fold higher high-voltage-activated (HVA) current density, a 10% smaller Ca 2+ -dependent inactivation, and L-type channels with 5 times slower activation and inactivation kinetics.…”
Section: The Melanotrope Neuroendocrine Transducer Cells Of the Southmentioning
confidence: 99%
“…Such Ca 2+ oscillations are generated at the plasma membrane through opening of N-type and R-type Ca 2+ channels (Lieste et al, 1998a; Zhang et al, 2005) and may drive the secretion of αMSH. By mobilizing intracellular calcium stores (“calcium-induced calcium release”; Koopman et al, 1999) the Ca 2+ influx also initiates a self-propagating Ca 2+ wave that enters the nucleus (Scheenen et al, 1996; Koopman et al, 2001) and possibly induces gene expression (Scheenen et al, 1994, 1996; Lieste et al, 1998b; Jenks et al, 2003; Van den Hurk et al, 2005b; Kuribara et al, 2010a).…”
Section: The Melanotrope Neuroendocrine Transducer Cells Of the Southmentioning
confidence: 99%